PENDIDIKAN MODERASI BERAGAMA DALAM AL-QUR'AN DAN HADITS - Fathoni (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
Islam as a divine religion in addition to teaching its followers to be obedient and obedient to its teachings but also teaches moderation towards other religions. In addition to moderation in matters of worship, it is also moderate in social life. Religious moderation is an interesting study because it is an integral core of Islamic teachings, Islam does not allow its people to carry out religious coercion. In a verse it is stated "To you is your religion and to me is my religion. This is a basis for religious moderation in Islam. Islam does not uphold violence and coercion in its teachings but on the contrary that Islam upholds hospitality and harmony in socio-religious relations between its followers and followers of other religions.